Paciente masculino de 8 años de edad con obesidad infantil - Velasco Macías, Nelly Mishell (2019)
The case study presents a male patient of 8 years of age who goes to the pediatric consultation for presenting dyspnea, fatigue, and diarrheic bowel problems in a number of 7 in 24 hours. Mother reports that the child complains of frequent abdominal pain in epigastrium of moderate intensity and is also accompanied by lack of energy generally in the day. Specialist doctor performs biochemical tests in which low hemoglobin and hyperlipidemia results. It presents a weight of 55kg and a height of 129cm, it is derived to the nutritionist for nutritional and anthropometric valuation corresponding.